Penguatan Pendidikan Karakter Selama Masa Pandemi Covid-19 di Sekolah Dasar - Guntoro, Guntoro; Santoso, Santoso; Utaminingsih, Sri (Universitas PGRI Semarang, 2022)
This research is motivated by the learning process during the covid 19 pandemic for students, especially in strengthening character education at SDN Rejosari 1. The objectives are: To describe the pattern of Character Education at home during the pandemic, To determine the results of the strengthening Learning assistance at home, To determine the implementation of values Character Education during the Covid 19 pandemic at SDN Rejosari 1. This research method uses a qualitative approach to the type of case study research. Research data collection techniques includes, interviews, observation, documentation. The collected data were analyzed by means of data reduction, data presentation, verification and triangulation. The results showed that there were four patterns used in the implementation of character education, namely through learning materials, school rules, student achievement awards and daily worship practices and spiritual guidance. The strengthening of character values at SDN Rejosari 1 goes through three stages, namely, the value transformation stage, the value transaction stage and the value trans-internalization stage. The strengthening of integrated character values in learning at SDN Rejosari 1 includes: religion, discipline, perseverance, curiosity, care, and responsibility, with the implementation of learning at home through whatsApp groups and learning assistance.